EVALUASI PROSES VERIFIKASI CALON ANGGOTA LEGISLATIF PADA PEMILIHAN UMUM LEGISLATIF 2014-2019 DI KOTA SEMARANG - Oshit Alesita Rinenggo; Purwoko .; Rina Martini (Journal of Politic and Government Studies, 2015)
The verification process of legislative candidates on legislative election 2014 in Semarang attracted a lot of attention in various circle enough. Verification is a gateway from search of qualified representative and clean from Corruption, Collution and Nepotism (KKN). Not only the political parties thah have to prepare everything for legislative elections. However, the election organizers such as the General Election Commission (KPU) should also show an attitude that cling to the principle of independence and professional.To determine the role of General Election Commission Semarang in verification of legislative candidates on legislative election 2014, the research using descriptive research method. These data were obtained from in-depth interviews as the primary data and some books as secondary data. Theory of the General Election Commission (KPU) and the theory of evaluation are used to ease in analyzing daa.Result of the research is the evaluation verification process of the legislative candidates on legislative election 2014 in Semarang basically already refers to the General Election Commission regulation No. 7/2013. But the implementation is not maximal. Because there are still problems that occur during the verification process, especially the problem of lack of socialization and establishment of DCS into DCT. So many constrains make the verification process has not been worked maximal that carried out by General Election Commission Semarang.Recommendation for next research is General Election Commission Semarang should be more cooperative and better coordination in improving the profesionalism and socializm that relate to what is the matters and needs that legislative candidates should know so that the verification process of legislative candidates can be maximal.Keywords: Verification, General Election Commission, Legislative Candidates